Charging performance evaluation of finned conical thermal storage system encapsulated with nano-enhanced phase change material - Singh, Rupinder Pal (2021)
This study introduces a novel latent heat storage system using a combination of active (fins and nanoparticles) and passive (conical design) heat transfer enhancement techniques for the solar absorption chilling system. First part of the work proposes a selection criterion using Multi-attribute decision making (MADM) combined with Multi objectives decision making (MODM) tools to rank and select the different nanoparticles. The methodology suggests Graphene as the best candidate amongst the widely used metal (Cu, Al, Ni, Ag) and metal oxide (CuO, Al₂ O₃ , TiO₂ , SiO₂) nanoparticles. Subsequently, the charging performance of the medium temperature eutectic salt (LiNO₃ -KCl; 50:50) dispersed with graphene nanoplates is studied in a conical shaped shell and tube storage system with & without fins. The numerical investigations are performed using the actual plant data of double effect solar absorption system. Based on the plant operating conditions, the Stefan and Grashoff numbers are obtained as 0.35 & 4.2 × 10⁵ respectively, showing the laminar flow of molten PCM. The thermal performance of the storage system coupled with heat transfer and fluid flow is studied for melt fraction, temperature field, the energy stored and heat flux variations at different concentration of graphene. Effect of enhanced viscosity and reduction in natural convection heat transfer due to GNP dispersion is studied simultaneously with the gained advantage of increased thermal conductivity. It is concluded that melting time is reduced by 57% using the proposed storage design in comparison with a conventional cylindrical system.